1998
DOI: 10.1136/jnnp.65.5.665
|View full text |Cite
|
Sign up to set email alerts
|

Right hippocampal contribution to visual memory: a presurgical and postsurgical study in patients with temporal lobe epilepsy

Abstract: Objectives-Existing speculations regarding the cognitive functions of the right hippocampus suggest a special involvement in non-verbal memory functions. However, all supporting evidence in epileptic patients came from postoperative studies that did not consider the preoperative functioning level. The present study investigates in patients with right temporal lobe epilepsy (RTLE), both preoperatively and postoperatively, the role of the right hippocampus for visual memory, visuoconstruction, and spatial visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
2
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 16 publications
12
77
2
7
Order By: Relevance
“…For the right temporal lobe there is some evidence that damage specifically in temporomesial structures may be the cause of impairments in non-verbal memory functions. Patients with hippocampal damage showed preoperatively [73] and postoperatively [74] impaired visual memory performance, whereas patients without hippocampal damage exhibited no deficiencies in visual memory. In line with previous operative studies, our results from MCI elderly adults with severe atrophy suggest a special involvement of MTA in visual memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…For the right temporal lobe there is some evidence that damage specifically in temporomesial structures may be the cause of impairments in non-verbal memory functions. Patients with hippocampal damage showed preoperatively [73] and postoperatively [74] impaired visual memory performance, whereas patients without hippocampal damage exhibited no deficiencies in visual memory. In line with previous operative studies, our results from MCI elderly adults with severe atrophy suggest a special involvement of MTA in visual memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were based on "learning capacity" (performance in the last trial, which has been shown to be sensitive for right temporal lobe dysfunction and right mesial pathology in right TLE. 24,25 Psychomotor speed/attention was assessed by a letter cancellation test. 26 Phonemic word fluency was assessed by a subtest of a German intelligence test.…”
Section: Cognitive Assessmentsmentioning
confidence: 99%
“…Damage incurred by left-sided mesial temporal lobe epilepsy is characterized by material-specific verbal memory deficits (Hermann et al, 1997). Analogous findings with right mesial temporal lobe epilepsy and non-verbal memory are less consistent, except for patients with hippocampal sclerosis, where specific visual memory deficits have been found (Gleissner et al, 1998a). This inconsistency may be partly dependent on the characteristics of the spatial cues, in particular how easily they can be verbalized (Barkas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%